Sedative, Hypnotic and Anti-anxiety Effects of Lignans from Schisandra chinensis Vine Stem in Mice - Hongxu CHEN; Liwei YUAN; Junxiong ZHANG; Wenxin WANG; Jiale LIU; Chunmei WANG; Jinghui SUN; Chengyi ZHANG; He LI; Jianguang CHEN (Shipin gongye ke-ji, 2022)
Objective: To study thesedative, anti-anxiety and hypnotic effects of Schisandra chinensis vine stem lignans (SSL) and its underlying mechanism. Methods: One hundred and fifty ICR male mice were evenly and randomly divided into 5 groups, namely the blank control group, the SSL low-dose group (35 mg/kg), middle-dose group (70 mg/kg), and high-dose group (140 mg/kg), and diazepam positive control group (4 mg/kg). All treatments were administered intragastrically, 0.1 mL/10 g and once daily for 7 days. The autonomous activities of mice were used to observe the sedative effect, the elevated plus maze and elevated zero Maze were used to observe the anti-anxiety effect. The synergistic sleep test of pentobarbital sodium at subthreshold and threshold doses was used to observe the hypnotic effect. Enzyme-linked immunosorbent assay (ELISA) was used to detect the content of γ-aminobutyric acid (GABA) and glutamate (Glu) in mouse brain tissue. Results: In comparison to the blank control group, the numbers of standing and spontaneous activities of the mice was significantly reduced (P<0.01) in all SSL groups. The open arm time, the numbers of open arm entry and open arm probe significantly increased (P<0.05 or P<0.01) in SSL middle- and high-dose groups. The number of sleep mice under the subthreshold dose of pentobarbital sodium increased in all SSL groups, the sleep latency was shortened and sleep time increased in mice under the threshold dose of pentobarbital sodium in all SSL groups (P<0.05 or P<0.01). The content of GABA in brain tissue significantly increased (P<0.01) in all SSL groups, while Glu content significantly decreased (P<0.01) and GABA/Glu ratio significantly increased (P<0.01) in SSL middle- and high-dose groups, and the expression of GABAAα1 protein in brain tissue of mice significantly increased (P<0.01) in SSL high-dose group. Conclusion: SSL had sedative, hypnotic and anti-anxiety effects in mice, the mechanism might be related to the regulation of GABA content in the brain tissue.